Kraft-tex creations : sew 18 projects with vegan leather : print, stitch, paint & design - Conner, Lindsay, 1983- (Stash Books, an imprint of C&T Publishing, 2019)
Print, paint, stamp, and stitch<U+2026> it<U+2019>s never been so fun to design as it is with kraft-tex! Discover the incredibly durable paper that looks, feels, and wears like leather, but sews just like fabric. Modern designers share twelve clever kraft-tex projects plus six bonus ideas, from bags and wallets to coasters and embroidered bracelets, proving there<U+2019>s something for everyone. Whether or not you<U+2019>ve used kraft-tex before, mixed-media artists and craft sewists will love its creative versatility.